Oppression Against Women In Margaret Eleanor Atwood's The Handmaid's Tale(1985) Novel: A Feminist Criticism - Rahmawati, Rizka Amalia, M. Thoyibi M.S, Titis Setyabudi, S.S, M.Hum (2013)
The major problem of this study is how oppresion against women is reflected in The Handmaid's Tale novel by Margaret Eleanor Atwood's. The objective of this study is to analyze the novel based on structural elements and to analyze the novel based on feminist criticism. In analyzing The Handmaid's Tale novel, the writer uses qualitative method and feminist criticism. The object of the study is Margaret EleanorTheHandmaid's Tale novel published in 1985. The data sources consist of primary data and secondary data sources. The primary data source is The Handmaid's Tale novel itself and the secondary data sources are the other sources related to the analysis such as books of literary theory, the author's biography, and the other relevant information to analysis of this research. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The results of the analysis shows the following conclusion: first, based on the structural analysis it can be concluded that in oppression in The Handmaid's Tale novel Margaret Eleanor Atwood's convey analysis that oppression is the condition that happens in all people especially of women. Second, based on the feminist criticism in The Handmaid's Tale novel,that there is a correlation between and social realities of America society in the twentieth century